Enhancing the effectiveness of sustainability partnerships : summary of a workshop - Vollmer, Derek (National Academies Press, 2009)
"Sustainable development---meeting human needs while nurturing and restoring the planet's life support systems---requires a continuous process of scientific innovation, new knowledge and learning, and collaborative approaches to implementing technologies and policies. To address these challenges, different stakeholder groups are increasingly seeking to ally themselves through partnership, in order to implement projects, deliver services, establish secure funding mechanisms, and achieve on the ground results. Advocates of this collaborative approach point to the failure of governmental regulations, international commitments, or business as usual. However, skeptics often question the effectiveness of partnerships at achieving sustainable development goals and, in the absence of demonstrated results, wonder where partnerships are adding value. A symposium held in June 2008 and summarized in this volume, attempted to advance the dialogue on partnerships for sustainability in order to catalyze existing knowledge and inform future efforts. Ideas that came out of discussions at the symposium will help leaders in government, the private sector, foundations and NGOs, and universities, both in the United States and internationally, as they develop and participate in new partnerships for sustainability.'--Publisher's description.